The effectiveness of the program based on mentalization and mindfulness (mother and child) in behavioral and emotional problems of primary school children - Darabi, Mostafa; Manavipour, Davood; Mohammadi, Akbar (Applied Family Therapy Journal (AFTJ), 2023)
Purpose: The purpose of this study was to investigate the effectiveness of the program based on mindfulness and mindfulness (mother and child) in behavioral and emotional problems of primary school children. Methods: This quasi-experimental research was pre-test-post-test and follow-up with a control group. The sampling method was voluntary. The volunteers of the experimental group were given a pre-test before the implementation of mentalizing interventions, and after the intervention, a post-test and the control group did not receive any intervention, but they also took a pre-test and a post-test. The sample group of first and second year primary school students had behavioral problems. The experimental group was trained in mindfulness sessions in eight sessions (Burdick, 2014). The research tool included the Achenbach-Child Behavior Inventory (Achenbach and Rescorella, 2007). In this research, analysis of variance with repeated measurements and Bonferroni's post hoc test were used to check the difference in means and data analysis was done with the help of SPSS 24 software. Results: The results showed that mentalization-based treatment on children's behavioral problems in the areas of anxiety/depression (F=78.35, P